Hybrid Learning as an Effective Learning Solution on Intensive English Program in the New Normal Era - Muhammad Nashir; Roudlotun Nurul Laili (Institut Agama Islam Negeri Palopo, 2021)
In this new normal era, the government has implemented new normal policies in various lines including education. This situation requires school community to adapt to this new normal era by complying with the health protocols set by the government. The lecturers as the main learning facilitator have very crucial role in forming new habits for students. Lecturers must be able to adapt in learning activities from the planning to its evaluation. Learning innovations and the usage of suitable and diverse media for learning significantly hold up enhancing the educational quality in the new normal era. One of the appropriate learning model solutions as a way to adapt in the new normal era is by applying hybrid learning in the Intensive English class. Hybrid learning model is a learning type which mixes face-to face and online by utilizing technological sophistication. This study aimed to explain hybrid as a form of learning solution on intensive English Program at Stikes Banyuwangi as an adaptation form to face the new normal era. The results of study indicated that hybrid learning make students easier in practicing the conversation during Intensive English class and can improve their learning outcomes and scores, especially in their speaking. 71.7% students stated that hybrid learning increase effectiveness, efficiency and their attractiveness, so it is quite effective to be applied. Then 85 students (81.8%) prefer hybrid learning than full online learning or totally face to face learning.